PENERAPAN MODEL PEMBELAJARAN THINK-PAIR-SHARE TERHADAP KOMPETENSI DASAR DEMOKRASI PADA SISWA KELAS VIII D SMP NEGERI 2 KEBAKKRAMAT TAHUN PELAJARAN 2011/2012 - ., Parsono . (PKn Progresif, 2015)
Based on the analysis results, the implementation of Think-Pair-Share method showed that defining democracy concept increased from 78% to 98%, elaborating the history of the first enforcement of democracy increased from 76% to 98%, explaining types of democracy implementation in nation?s life, increased from 79% to 97%, and explaining the nature of Pancasila democracy and its implementation in nation?s life increased from 81% to 96%. These results denoted that Think-Pair-Share method could improve the Civic Educationsubject performance in showing participation in nation defense effort. Think-Pair-Share is a right initial step to motivate students to follow the next stage of learning. Moreover, in this step, students are given chances to decide their answer and the problems delivered by the teachers, and write their own ideas, so that the individual thinking ability can be improved. This step is more effective than when the teacher presents a problem or a question, and asks the answer to the students one by one. In the next activity, which is a discussion with a partner, students who never or rarely speak in front of the class can be able to express his/her ideas to the partner.